Analisis Statistik Aspek Biologi Wild Betta (Betta imbellis) Sebagai Pendukung Bahan Ajar Mata Kuliah Ekologi Hewan - Putri Amanda Ramadani; Khairul; Ilham Hakiki Harahap (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze statistical data related to the biological aspects of Betta imbellis as teaching material for the Animal Ecology course. The method used was purposive sampling at two different locations. A total of 30 individuals (15 individuals per location) were captured using a traditional fish trap, then measured using a digital caliper and weighed with a digital scale. The observed parameters included morphometric, meristic, length-weight relationship, sex ratio, and condition factor. Data were analyzed using Microsoft Excel 2013 and SPSS version 22. The results showed differences in morphometric (DBL, ABL, CPD, LUCL, LMCL, LCLL) and meristic (AR) characters between populations. The growth pattern was negative allometric (b < 3). The male-to-female sex ratio was 2:1, while the condition factor ranged from 1.82–2.05 (K) and 245.76–455.70 (Wr). In conclusion, these findings provide preliminary data to support conservation efforts of wild Betta imbellis and serve as teaching material for the Animal Ecology course. Keywords: Analysis Statistical, Biological Aspects, Betta imbellis